ASSOCIATION OF POLYMORPHISMS IN PROLACTIN RECEPTOR AND MELATONIN RECEPTOR 1C GENES ON EGG PRODUCTION AND EGG QUALITY TRAITS OF JAPANESE QUAILS (COTURNIX COTURNIX JAPONICA) - L. T. T. Lan; #; N. T. H. Nhan; #; L. T. Hung; R. L. Soubra; T. T. Gia; L. H. Anh; N. H. Xuan; N. T. Ngu (Journal of Animal and Plant Sciences, 2021)
In the present study, the association between a 24-bp Insertion-Deletion (Indel) in the prolactin receptor gene (PRL), and the polymorphic site NC_006091.5: c.25.144.C>A(T) in the melatonin receptor gene (MTNR-1C) was investigated in Japanese laying quails. In total, 396 female and 132 male quails were selected for the experiment. The number of eggs was recorded daily in individual quails for egg production and other reproductive traits. Every four weeks, one egg per quail was randomly selected for external and internal assessment. PCR-RFLP and PCR-SSCP were applied for genotyping the Indel, and the single nucleotide polymorphism in PRL and MTNR-1C genes, respectively. The data was continuously collected until 48 weeks of laying. For the effects of PRL Indel, it was found that DD genotyped quails provided a slightly higher egg yield in the first 24 laying weeks (155.1 eggs/quail); however, when the quails reached 36 and 48 weeks of laying, the difference in egg production was clear (P<0.05) in quails with II genotype (213.0 and 281.9 eggs/quail, respectively). In the MTNR-1C gene, six genotypes were detected at the polymorphic site, of which AA and AT genotyped quails were better for egg yield in comparison with those baring other genotypes. For egg quality, only albumen weight and albumen ratio differed from quails with II genotype to those of other quails in the 1-24 laying weeks. In the later period (25-48 weeks), yolk index was the highest in quails baring DD genotype. For the MTNR-1C polymorphism, the differences (P<0.05) were found in traits related to albumen and yolk; however, no genotype really stands out in terms of egg quality. In conclusion, the two polymorphisms studied may be utilized in breeding programs to enhance egg yield and egg quality traits in Japanese quails of which the PRL (II) and MTNR-1C (AA) alleles are suggested.
Keywords: Association; egg traits; Japanese quails; MTNR-1C; PRL